Advances in Coaxial Additive Manufacturing and Applications. Issue 11 (16th July 2021) - Rafiee, Mohammad; Granier, Floriane; Therriault, Daniel
Abstract: Coaxial additive manufacturing (AM) is an emerging technology involving the simultaneous deposition of two or more materials with a common longitudinal axis. It has the potential to overcome the disadvantages associated with conventional single‐material AM for the production of core‐shell or multi‐core‐shell multimaterial structures. The coaxial AM techniques can be classified into extrusion and material jetting technologies. The extrusion‐based technologies rely on the co‐extrusion of multiple materials through a coaxial nozzle whereas the material jetting technologies are based on the introduction of a high voltage electric field between a coaxial nozzle and a grounded collector plate. This review is aimed to provide a comprehensive overview of multimaterial coaxial AM, including the technologies, nozzle designs, materials, and applications. The advances in coaxial AM and the benefits of this novel technology in various fields are highlighted. For instance, in biomedicine coaxial AM offers an exciting alternative to single‐material bioprinting for the fabrication of bio‐scaffolds and vascular networks as well as for tissue engineering and cell encapsulations. Coaxial AM is also a subject of growing interest in the fields of flexible sensors, e‐textiles, and printed electronics. Perspectives on the limitations, existing challenges, opportunities, and future directions for further development are also provided. Abstract : Coaxial additive manufacturing is particularly attractive due to its unique feature of simultaneously depositing two or more materials with a common axis. This feature benefits various fields from biomedical and tissue engineering to electronics and composites. The present work compares coaxial additive manufacturing technologies, discusses advantages and disadvantages, and provides future directions.